EXPLORING THE SUCCESS FACTORS OF KRING! (2020) AND BATIK GIRL (2019) - Edrina, SN; Norhasheila, M; Nurshafira, MRN; Nabila, AA; Syuhaidi, ABM (Proceeding of the International Conference on Arts and Humanities, 2023)
The Malaysian animation industry has produced many animated short films and have claimed success through various forms. Among the successful short animations produced, Kring! (2020) created by BrainyBones Studio and Batik Girl (2019) created by R&D Studio are the two short, animated films produced locally that have received a number of notable awards across the world. The development and export of original IPs shows that the Malaysian animation sector, like the rest of the region, is maturing. These well-known works have employed a variety of variables, tactics, and aspects to attain their current popularity, thus the goal of this article is to figure out what factors, strategies, or elements were used in these award-winning films. This study has employed a qualitative research design with the use of semi structured interviews from the producers and creators behind these two films. At the conclusion of this study, it is possible that it will provide achievement for the animation film industry for future short animation film producers, which will be crucial in boosting the number of successful projects in the local sector.